United Kingdom : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This Selected Issues paper examines the operational independence and the conduct of monetary policy in the United Kingdom. The paper describes the inflation targeting framework and the analytics of the decision-making process. It suggests that inflation targeting, although not entirely new in terms of the basic idea, is a rather significant step toward establishing a workable and well-defined framework for monetary policy. The paper also describes structure, mandate, and policy issues associated with the financial services authority.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet